Psychological Well-Being Santri scale (PWBSs): Construct validity with Confirmatory Factor Analysis - Suprananto, Suprananto; Samudera, Arung; Hamdi, M. Dudih Fadilah (TAZKIYA Journal of Psychology, 2024)
The Psychological Well-Being of Santri is a measuring instrument that aims to measure the Psychological Well-Being of Santri. Therefore, this study aims to test the construct validity of this measuring instrument. PWBSs includes six subscales, each consisting of 4 items designed to measure the dimensions of the psychological well-being of santri as follows: 1) Personal, 2) Emotional, 3) Social, 4) Physical, 5) Spiritual, 6) Cognitive. The total sample in this study was 595 respondents. Consisting of 334 males and 261 females aged between 12-25 years. Samping in this study used probability sampling techniques using random sampling techniques. The analysis method used is Confirmatory Factor Analysis (CFA) with the help of Lisrel 8.7 software. The test results prove that there are 43 items that are in accordance with the data and 21 items in psychological well-being instrument of santri measure more than one factor or do not match the data. The researchers suggested that these 21 items be revised from the measuring instrument because they measure more than one factor.